Real-time environmental forecasts of the Chesapeake Bay: Model setup, improvements, and online visualization. (June 2021) - Bever, Aaron J.; Friedrichs, Marjorie A.M.; St-Laurent, Pierre
Abstract: Daily real-time nowcasts (current conditions) and 2-day forecasts of environmental conditions in the Chesapeake Bay have been continuously available for 4 years. The forecasts use a 3-D hydrodynamic-biogeochemical model with 1–2 km resolution and 3-D output every 6 h that includes salinity, water temperature, pH, aragonite saturation state, alkalinity, dissolved oxygen, and hypoxic volume. Visualizations of the forecasts are available through a local institutional website (www.vims.edu/hypoxia ) and the MARACOOS Oceans Map portal (https://oceansmap.maracoos.org/chesapeake-bay/ ). Modifications to real-time graphics on the local website are routinely made based on stakeholder input and are formatted for use on a mobile device. Continuous model input files were developed from daily real-time forecast input files, for hindcast simulations and efficient evaluation and improvement of the real-time model. This manuscript describes the setup of the environmental forecasting system, how the model accuracy has been improved, and the revision of online graphics based on stakeholder feedback. Highlights: A real-time environmental forecast system of the Chesapeake Bay has run since 2017. Forecast includes salinity, temperature, oxygen, and acidification metrics. Current conditions and 2-day forecasts are available on a mobile-friendly website. Visualizations are updated regularly based on stakeholder feedback. Model output is available on a THREDDS server for use by others via MARACOOS.